Refolding of ribonuclease A monitored by real-time photo-CIDNP NMR spectroscopy. - Day, I; Maeda, K; Paisley, H; Mok, K; Hore, P (2009)
Photo-CIDNP NMR spectroscopy is a powerful method for investigating the solvent accessibility of histidine, tyrosine and tryptophan residues in a protein. When coupled to real-time NMR, this technique allows changes in the environments of these residues to be used as a probe of protein folding. In this paper we describe experiments performed to monitor the refolding of ribonuclease A following dilution from a high concentration of chemical denaturant. These experiments provide a good example of the utility of this technique which provides information that is difficult to obtain by other biophysical methods. Real-time photo-CIDNP measurements yield residue-specific kinetic data pertaining to the folding reaction, interpreted in terms of current knowledge of the folding of bovine pancreatic ribonuclease A.